PENERAPAN PEMBELAJARAN BILINGUAL DALAMMEMPERSIAPKAN SISWA MENGHADAPI TANTANGAN DALAMREVOLUSI INDUSTRI 4.0 - Andi Hermawan; Rina Yuliana; Damanhuri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to provide an overview of the implementation of two languages or bilingual (Indonesian and English) learning to face the challenges of the industrial revolution 4.0. Through a descriptive approach, this study was conducted at SDIT Widya Cendekia, Serang. The researchers conducted interviews, observation, and documentation to obtain the data. The subjects of this study were the principal, the homeroom teachers, and students of SDIT Widya Cendekia, Serang. The learning implementation in the bilingual class followed the national curriculum and school curriculum, and bilingual learning was conducted by implementing a project-based learning model and a scientific approach. It aimed that students would have 4C skills (Critical Thinking, Communication, Collaboration, Creativity, and Innovation) to deal with the challenges in the industrial revolution 4.0.